Development of a measure of receptivity to instructional feedback and examination of its links to personality. (1st February 2021) - Lipnevich, Anastasiya A.; Gjicali, Kalina; Asil, Mustafa; Smith, Jeffrey K.
Abstract: The purpose of this study was to report on the construction of an instrument to measure receptivity to instructional feedback (RIF) and provide initial validity evidence for its use. We also explored the degree to which students' receptivity of instructional feedback was associated with their the Big Five personality traits of Conscientiousness, Agreeableness, Neuroticism, Openness, and Extraversion. Confirmatory Factor Analysis suggested that the 4-factor initially hypothesized model that comprised experiential attitudes, instrumental attitudes, cognitive engagement with feedback, and behavioural engagement with feedback componets had good model fit. Out of the five personality dimensions, Conscientiousness and Openness were the strongest predictors of the receptivity components, especially of students' behavioural engagement with feedback. This study presents initial validity evidence of the utility of the RIF scale. Highlights: This study provides measurement validity evidence of a receptivity to feedback scale. Openness and Conscientiousness are strong predictors of all receptivity factors. Emotional instability is predictive of cognitive engagement with feedback. Personality factors explain up to 25% of the variability in receptivity.